A highly stretchable, ultra-tough, remarkably tolerant, and robust self-healing glycerol-hydrogel for a dual-responsive soft actuator. Issue 45 (4th November 2019) - Guo, Meiling; Wu, Yuanpeng; Xue, Shishan; Xia, Yuanmeng; Yang, Xi; Dzenis, Yuris; Li, Zhenyu; Lei, Weiwei; Smith, Andrew T.; Sun, Luyi
Abstract : A novel strategy to synthesize a glycerol-hydrogel with high stretchability, ultra-toughness, remarkable tolerance, and outstanding self-healing capability has been developed. A soft actuator has been fabricated based on the glycerol-hydrogel. Abstract : Stimuli-responsive devices based on stretchable, tough, tolerant, and self-healing hydrogels are critical to fabricate soft actuators but it remains a formidable challenge to develop them. Herein, a novel strategy is demonstrated to meet this challenge by incorporating functionalized boron nitride nanosheets (nano-reinforcing domains) into poly(acrylamide- co -maleic anhydride) (soft elastin matrix) hydrogel followed by glycerol–water post-treatment. The resultant glycerol-hydrogel exhibited high stretchability (strain at break up to 2700%), outstanding tensile strength and toughness (up to 2.8 MPa and 19.3 MJ m −3, respectively), long-term dehydration resistance to high temperature (60 °C), and excellent anti-freezing properties at low temperature (−45 °C). Furthermore, excellent self-healing capability was demonstrated by the healing of the hydrogel after three months of storage at temperatures as low as −45 °C. By taking advantage of the outstanding dehydration resistance of the glycerol-hydrogel, dual responsive actuating devices were designed based on bilayer hydrogels to grip, release, and drive a ball under different stimuli. Thus, this work not only inspires the design and fabrication of high-performance hydrogels but also broadens their applications in soft robotics, bioactuators, and other areas.